A function-oriented approach to transport planning in Sweden: Limits and possibilities from a policy perspective. (April 2018) - Johansson, Fredrik; Tornberg, Patrik; Fernström, Astrid
Abstract: Research on sustainability and transport has paid increasing attention to how the purpose of the transport system is framed, often arguing that there is a need to shift the focus of transport planning and policy from the physical infrastructure to mobility and accessibility. Sweden's national transport policy also has elements of this shift, most noticeable in the so-called four step principle, where the possibility to affect the need for transport and choice of transport mode (step 1) and the possibility to use existing infrastructure more efficiently (step 2) should be considered before large reconstructions (step 3) or new infrastructure (step 4) is chosen as the solution to transport related problems. The aim of this article is to study whether the practical implications of Swedish national transport policy are consistent with the ambitions expressed in the four step principle, with particular focus on the Swedish Transport Administration's (STA) mandate to finance different measures. Based on an analysis of policy documents and semi-structured interviews the main finding of the analysis is that many step 1 and 2 measures do not fall within the financial mandate of the STA. The implementation of the four step principle therefore depends on the commitment among other actors than the STA to implement step 1 and 2 measures. Furthermore, it is concluded that the limits to the STA mandate has consequences for the ability of the STA to engage in collaboration with the actors on which it depends, and that strengthening the STA's mandate to finance a desired function rather than physical infrastructure is likely to increase commitment among other stakeholders to work with these measures. Such a step would imply a different regulatory framework than the current, more in line with "the sustainable mobility paradigm" (Banister 2008) and could contribute to a good accessibility to different amenities at the same time as negative environmental impacts are reduced. Highlights: Sweden's transport policy is increasingly focusing on accessibility. The STA's financial mandate is not consistent with this change of focus. Proposal to give the STA a financial mandate based on desired functions.